2018
DOI: 10.1186/s13019-018-0737-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ventilation/perfusion ratio map in surgical patients by dual-energy CT after xenon inhalation and intravenous contrast media

Abstract: BackgroundWhile many studies have evaluated the change in lung volume before and after lung resection and correlated this with pulmonary function test results, there is very little evidence on the changes in ventilation perfusion ratio (V/Q) before versus after lung resection. In the present pilot study, we evaluated if V/Q mapping can be constructed using dual energy CT images.MethodsThirty-one lung cancer patients planned for pulmonary resection were included in this study. To evaluate ventilation, Xenon-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Due to the complex anatomy of the mediastinum, it is easy to involve surrounding vital structures in a procedure for a locally advanced thymic tumor; this makes the procedure unpredictable and broad. The types of surgery for cases that involve adjacent anatomies to the thymic tumor are listed as follows: If a vascular structure is involved, such as a replacement of the vena cava [ 50 ] or complicated replacement of the aortic arch and its branches [ 51 ]; If a lung is involved, such as lung resection [ 52 ] or extrapleural pneumonectomy [ 53 ]; Specific surgical incisions, such as the common median sternotomy [ 14 ] or the clamshell incision [ 54 ]. …”
Section: Debatable Issues About Surgery For Thymic Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complex anatomy of the mediastinum, it is easy to involve surrounding vital structures in a procedure for a locally advanced thymic tumor; this makes the procedure unpredictable and broad. The types of surgery for cases that involve adjacent anatomies to the thymic tumor are listed as follows: If a vascular structure is involved, such as a replacement of the vena cava [ 50 ] or complicated replacement of the aortic arch and its branches [ 51 ]; If a lung is involved, such as lung resection [ 52 ] or extrapleural pneumonectomy [ 53 ]; Specific surgical incisions, such as the common median sternotomy [ 14 ] or the clamshell incision [ 54 ]. …”
Section: Debatable Issues About Surgery For Thymic Tumorsmentioning
confidence: 99%
“…Specific surgical incisions, such as the common median sternotomy [ 14 ] or the clamshell incision [ 54 ].…”
Section: Debatable Issues About Surgery For Thymic Tumorsmentioning
confidence: 99%
“…By combining these data with spectral iodine perfusion scans, a ventilation/perfusion CT can be constructed. 207,208 Since iodine and xenon have similar attenuating features, it is not possible to discriminate them on a single spectral CT. However, by replacing iodine with gadolinium as an intravenous contrast agent, it has been demonstrated that it is feasible to acquire a ventilation/perfusion CT with one spectral scan through threematerial differentiation.…”
Section: Functional Sparing Of Organs-at-riskmentioning
confidence: 99%
“…Chest and sinus CT is typically used in CF to detect early lung disease/bronchiectasis and mucus-plugging, respectively [ 30 , 37 ]. Moreover, HRCT is used for detecting the impact of exacerbations and lung disease progression, where CT-based functional analysis using 3D reconstruction of the airway and pulmonary vasculature allows the quantification of airflow obstruction, changes in airway size, and/or blood volume in pulmonary vasculature [ 34 , 55 , 56 , 57 ]. Similarly, advances in magnetic resonance imaging (MRI)-based functional imaging and X-ray-fluoroscopy-based ventilation and lung heterogeneity analysis allow the quantification of regional lung function changes to predict prognosis and efficacy of interventions [ 28 , 29 , 30 , 34 , 55 , 57 ].…”
Section: Functional Lung Imaging Modalities For Evaluating Cystic mentioning
confidence: 99%